Limb salvage after severe Klebsiella pneumonia infection following ipsilateral total hip and knee arthroplasty- A case report and literature review. (Journal of Pakistan Orthopaedic Association, 2021)
Total hip and knee replacement is one of the most common procedure in the world. Infection of the hip and knee replacement could be devastating. The infection rate after primary arthroplasty is 1% to 2% and after revision arthroplasty is 2.5% to 3.2%. The infection of ipsilateral hip and knee is a rare condition. We are presenting a case of 48 years old female who presented to us with this condition. She had Klebsiella Pneumonia infection of the ipsilateral hip and knee. She undergone removal of the total hip and total knee implants followed by multiple debridement and irrigation of the femur and tibia. Later on revision total hip arthroplasty was done with custom design prosthesis and knee arthrodesis at the ipsilateral knee. Patient did very well and manage to walk out of the hospital. We managed to salvage the limb with good outcome.